问题 解答题
用简便方法计算下面各题.
2
5
+
9
14
+
5
14
=
1
4
+
3
7
+
3
4
+
4
7
=
11
20
+
4
9
+
9
20
-
4
9
=
6
7
-(
4
7
+
1
14
)
=
11
18
-
5
8
+
17
18
-
3
8
=
6-
2
7
-
5
7
=
9
16
-(
3
4
-
3
16
)
=
2
7
+(
3
5
+
1
7
)-
1
5
=
答案

(1)

2
5
+
9
14
+
5
14

=

2
5
+(
9
14
+
5
14
),

=

2
5
+1,

=1

2
5

(2)

1
4
+
3
7
+
3
4
+
4
7

=(

1
4
+
3
4
)+(
3
7
+
4
7
),

=1+1,

=2;

(3)

11
20
+
4
9
+
9
20
-
4
9

=(

11
20
+
9
20
)+(
4
9
-
4
9
),

=1+0,

=1;

(4)

6
7
-(
4
7
+
1
14
),

=

6
7
-
4
7
-
1
14

=

2
7
-
1
14

=

3
14

(5)

11
18
-
5
8
+
17
18
-
3
8

=(

11
18
+
17
18
)-(
5
8
+
3
8
),

=1

5
9
-1,

=

5
9

(6)6-

2
7
-
5
7

=6-(

2
7
+
5
7
),

=6-1,

=5;

(7)

9
16
-(
3
4
-
3
16
),

=

9
16
-
3
4
+
3
16

=

9
16
+
3
16
-
3
4

=

3
4
-
3
4

=0;

(8)

2
7
+(
3
5
+
1
7
)-
1
5

=

2
7
+
3
5
+
1
7
-
1
5

=(

2
7
+
1
7
)+(
3
5
-
1
5
),

=

3
7
+
2
5

=

29
35

单项选择题
单项选择题